High-ET isolated-photon plus jets production in pp collisions at s√= 8 TeV with the ATLAS detector - Aaboud, M. (2016)
The dynamics of isolated-photon plus one-, two- and three-jet production in pp collisions at a centre-of-mass energy of 8 TeV are studied with the ATLAS detector at the LHC using a data set with an integrated luminosity of 20.2 fb-1. Measurements of isolated-photon plus jets cross sections are presented as functions of the photon and jet transverse momenta. The cross sections as functions of the azimuthal angle between the photon and the jets, the azimuthal angle between the jets, the photon-jet invariant mass and the scattering angle in the photon-jet centre-of-mass system are presented. The pattern of QCD radiation around the photon and the leading jet is investigated by measuring jet production in an annular region centred on each object; enhancements are observed around the leading jet with respect to the photon in the directions towards the beams. The experimental measurements are compared to several different theoretical calculations, and overall a good description of the data is found.